Луысал ке ваньзэ вераме: кылбуръёс, поэмаос / Николай Байтеряков - Байтеряков Николай Семенович (Удмуртия, 1992)
Экземпляры: аб. ЦБ (1993) / Инвентарный номер: 34977 / Цена: / Сис.шифр: С(Удм) / Авт.знак: Б 18 / ГРНТИ: 17.82.10 / ББК: 84(Удм)^VLBC/RL